Enantioselective Synthesis of Tertiary Trifluoromethyl Carbinols by Vinylogous Aldol Reaction of 3-Methylcyclohex-2-en-1-one with (Het)aryl Trifluoromethyl Ketones - Chen, Fenfen; Chang, Zhixin; Paidamoyo, Chigumbu; Zeng, Xiaofei; Wang, Yongjiang; Han, Xiaoyu (Synlett, 2019)
A direct enantioselective vinylogous aldol reaction of trifluoromethyl ketones with 3-methylcyclohex-2-en-1-one through hydrogen-bond-directing dienamine catalysis by a diamine–sulfonamide catalyst has been demonstrated. A range of trifluoromethylated tertiary alcohols were efficiently produced in yields of up to 86% and with 93% enantioselectivity.
Keywords: organocatalysis; enantioselectivity; vinylogous aldol reaction; asymmetric catalysis; trifluorohydroxypropylcyclohexenones; aryl trifluoromethyl ketones